(untitled) (Agriculture, Food, and Natural Resources Journal, 2024)
Cardiovascular diseases (CVDs) remain a leading cause of mortality and morbidity worldwide, making effective prevention and management strategies crucial. This systematic review aimed to synthesize the current evidence on dietary management strategies for CVDs. A comprehensive literature search was conducted to identify relevant studies published between January 2017 and March 2024, focusing on dietary interventions, patterns, and components related to CVDs prevention and management. Three main themes emerged: 1) dietary patterns, 2) specific dietary components, and 3) emerging dietary interventions. The Mediterranean and Dietary Approaches to Stop Hypertension diets, rich in plant-based foods, whole grains, lean proteins, and healthy fats, were consistently associated with reduced CVDs risk and improved cardiovascular health outcomes. Specific dietary components, such as whole grains, fiber, plant-based proteins, and omega-3 fatty acids, exhibited protective effects against CVDs, while high consumption of saturated and trans fats, added sugars, and sodium increased the risk. Emerging interventions, including time-restricted feeding, intermittent fasting, and the incorporation of nutraceuticals and functional foods, showed promising results in improving cardiovascular risk factors, although further research is needed to establish their long-term efficacy and mechanisms of action. This review highlights the importance of adopting healthy dietary patterns and emphasizing nutrient-dense foods in the prevention and management of CVDs. Future research should focus on investigating the potential synergistic effects of combining dietary interventions with other lifestyle modifications and exploring personalized approaches to optimize cardiovascular health outcomes.